The civil rights movement : an eyewitness history - Wexler, Sanford (New York, NY : Facts on File, 1993)
Uses speeches, articles, and other writings of those involved to trace the history of the civil rights movement in the United States, primarily from 1954 to 1965
Includes bibliographical references (p. 337-348) and index
Keywords: African Americans -- Civil rights -- Juvenile literature; Civil rights movements -- United States -- Juvenile literature; Civil rights movements -- History -- Sources; African Americans -- Civil rights; Race relations -- History -- Sources; United States -- Race relations -- Juvenile literature